A comparative study of spinal bupivacaine with fentanyl versus ultrasound-guided combined lumbar plexus and sciatic nerve block in lower limb orthopedic procedures: A prospective randomized controlled trial. - Lathika G; Dr. Rajaram M; Elakkiya.G; Periasamy, Panneerselvam (Student’s Journal of Health Research Africa, 2025)
Background Spinal anesthesia with bupivacaine and fentanyl is widely used for its rapid onset, while ultrasound-guided lumbar plexus and sciatic nerve blocks are gaining popularity for prolonged postoperative analgesia with fewer systemic side effects. Aim: To compare the efficacy of spinal bupivacaine with fentanyl versus ultrasound-guided combined lumbar plexus and sciatic nerve blocks in lower limb orthopedic procedures. Methods This prospective randomized controlled trial was conducted on 50 patients aged 18–65 years undergoing elective lower limb orthopedic surgeries. Patients were randomized into two groups: Group A received spinal bupivacaine (12.5 mg) + fentanyl (25 mcg); Group B received ultrasound-guided lumbar plexus block with 30 ml of 0.25% bupivacaine and sciatic nerve block with 25 ml of 0.25% bupivacaine. Primary outcomes included onset and duration of sensory and motor blocks, and duration of analgesia. Secondary outcomes included hemodynamic changes and complications. Results Both groups were comparable in baseline demographics, with a mean age of 49 years and a similar distribution of sex and ASA physical status. The onset of sensory and motor block was significantly faster in Group A (5–8 min and 6–10 min) compared to Group B (10–20 min and 12–20 min; p<0.001). However, Group B had a significantly longer duration of sensory block (6–8 hrs), motor block (3–4 hrs), and analgesia (8–12 hrs) (p<0.001). Hypotension was more common in Group A (48%) than in Group B (32%). Two patients in Group B required conversion to general anesthesia due to technical difficulties. Conclusion Ultrasound-guided lumbar plexus and sciatic nerve blocks provide longer postoperative analgesia with fewer hemodynamic changes, making them preferable in high-risk or prolonged orthopedic surgeries. Recommendations For lower limb orthopedic surgeries, ultrasound-guided lumbar plexus and sciatic nerve blocks are recommended, particularly in patients at risk of hemodynamic instability or requiring prolonged analgesia.